Anterior shoulder instability in throwers and overhead athletes: Long-term outcomes in a geographic cohort - Wilbur, R. R.; Shirley, M. B.; Nauert, R. F.; LaPrade, M. D.; Okoroha, K. R.; Krych, A. J.; Camp, C. L. (The American Journal of Sports Medicine, 2021)
Background: Athletes of all sports often have shoulder instability, most commonly as anterior shoulder instability (ASI). For overhead athletes (OHAs) and those participating in throwing sports, clinical and surgical decision making can be difficult owing to a lack of long-term outcome studies in this population of athletes.